Description of knowledge, Behavior of Vegetable and Fruit Consumption, and Nutritional Status in Class X Students in Public High School 1 Porong Sidoarjo - Shelineroos Wananda Putri Sheline; Nur Hatijah; Mujayanto; Nuning Marina Pengge; Fahmi Hafid; Sarina Sariman (Journal of Nutrition Explorations, 2024)
In Indonesia, according to the 2018 Basic Health Research report, the majority of the population above the age of 5, which is around 95.5%, still consumes vegetables and fruits below the recommend levels. When a person's knowledge and behavior are not optimal, then they will have difficulty maintaining the balance of food intake they consume. The purpose of the study was to determine the description of knowledge, fruit vegetable consumption behavior and nutritional status in class X students at SMA Negeri 1 Porong. This was a descriptive study. The Sampling method used was simple random sampling  with a total samples size of  40 people. The results showed that the knowledge level of respondents in the poor category was 18 adolescents and in the good category was 11 adolescents. Most adolescents (34) exhibited poor vegetable consumption behavior, while the majority (21) demonstrated good fruit consumption behavior. The nutritional status of most respondents had good nutritional status as many as 25 adolescents. In Conclusion, adolescents in SMA Negeri 1 Porong have knowledge about vegetables and fruits in the poor category, poor vegetable consumption behavior, good fruit consumption behavior and good nutritional status.